Good Governance Principles in Buddhism for Corporate Social Responsibility to Sustainable Balanced Development - Sakajai, Supaphida; Khobjai, Attayawan; Donpan, Rattanakorn; Dasungnoen, Jaruwan; Srijaiwong, Sukhonthip; Rojanatrakul, Tanastha (Journal of Thammawat, 2024)
The application of the principles of good governance in Buddhism, which were based on the foundation of correctness, goodness, and stability, would enable the organization to increase its administrative efficiency. It was also a mechanism for monitoring and inspection, with the participation of the public or external organizations. This was to prevent damage to the organization’s administration because creating good governance in the organization was creating a good sense of administration and work in the organization, organizing a system that supported the practice of good sense, whether in terms of efficient administration, no waste, monitoring corruption, transparency, taking into account those who would be affected, both the government sector, the private sector, and the public.